Risk factors for the presence of dengue vector mosquitoes, and determinants of their prevalence and larval site selection in Dhaka, Bangladesh. - Kishor Kumar Paul; Parnali Dhar-Chowdhury; C Emdad Haque; Hasan Mohammad Al-Amin; Doli Rani Goswami; Mohammad Abdullah Heel Kafi; Michael A Drebot; L Robbin Lindsay; Gias Uddin Ahsan; W Abdullah Brooks (PLoS ONE)
Dengue viruses are responsible for over 100 million infections a year worldwide and are a public health concern in Bangladesh. Although risk of transmission is high, data on vector population characteristics are scanty in Bangladesh; therefore, a comprehensive prediction of the patterns of local virus transmission is not possible. Recognizing these gaps, multi-year entomological surveys were carried out in Dhaka, where the disease is most frequently reported. The specific objectives of the present study are threefold: i) to determine the risk factors for the presence of Aedes mosquitoes; ii) to identify the types of most productive and key containers; and iii) to estimate the effects of climatic factors on Aedes abundance in the city of Dhaka, Bangladesh. Entomological surveys were conducted in 12 out of 90 wards in Dhaka. These wards were selected using a probability proportional sampling procedure during the monsoon seasons in 2011, 2012 and 2013 and in the dry season in 2012. All containers inside and around sampled households were inspected for mosquito larvae and pupae, and containers were classified according to their relative size, use pattern, and materials of construction. During the study period (2011-2013), 12,680 larvae and pupae were collected. About 82% of the identified immature mosquitoes were Aedes aegypti, while the remainder were Ae. albopictus and other mosquito species. The largest number of immature mosquitoes was collected from tires and refrigerator trays during 2011 and 2012 monsoon seasons. Conversely, plastic drums were the most productive during the 2012 dry and 2013 monsoon season. Vehicle parts and discarded construction materials were the most efficient producers of Aedes mosquitoes in all surveys. The presence of Aedes mosquitoes was significantly (p < 0.05) higher in low socio-economic zones of Dhaka. Container location, presence of vegetation, and availability of shade for containers were also significantly associated with finding immature Aedes mosquitoes, based on multivariable analysis after confounder adjustment. Rainfall, temperature, and relative humidity also significantly affected the mean abundance of mosquitoes. Proper use, disposal, and recycling of the containers that effectively produce large numbers of Aedes vector mosquitoes may decrease the risk of arboviral transmission.